Effectiveness comparison of nifedipine, methyldopa, and labetalol in severe preeclampsia: A systematic review - Rahardjo, Bambang; Rahajeng; Nurhaeni, Yohanes Rico (Universitas Airlangga, 2026)
HIGHLIGHTS All three medications (nifedipine, methyldopa, and labetalol) are viable first-line options for treating severe preeclampsia in pregnanc Oral nifedipine may be faster at lowering blood pressure in severe preeclampsia than methyldopa or labetalol. ABSTRACT Objectives: Nifedipine, methyldopa, and labetalol are commonly used antihypertensive drugs for the management of severe preeclampsia. However, evidence directly comparing their effectiveness remains limited. This systematic review aimed to evaluate and compare the effectiveness of nifedipine, methyldopa, and labetalol in achieving blood pressure control in pregnant women with severe preeclampsia. Materials and Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted in MEDLINE (PubMed), ScienceDirect, and the Cochrane Library for studies published between May 2014 and May 2024. Randomized controlled trials evaluating nifedipine, methyldopa, and/or labetalol in pregnant women with severe preeclampsia were included. Eligible studies were screened and assessed using predefined criteria, and relevant data were extracted and analyzed qualitatively. Results: A total of 12 randomized controlled trials met the inclusion criteria and were included in the qualitative synthesis. All participants in the included studies met the diagnostic criteria for severe preeclampsia and received antihypertensive therapy. Overall, nifedipine demonstrated a higher rate of achieving target blood pressure compared with methyldopa and labetalol in most studies. Labetalol also showed good effectiveness in controlling severe hypertension, whereas methyldopa generally had a slower onset of action and lower efficacy in reaching target blood pressure. Conclusion: All three medications remain viable first-line options for the management of severe preeclampsia during pregnancy. However, when only a single antihypertensive agent is available, nifedipine or labetalol may be preferred over methyldopa. Oral nifedipine appears to provide faster blood pressure reduction in severe preeclampsia.